2017
DOI: 10.1002/jor.23558
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of native and tissue‐engineered cartilage toward understanding the pathogenesis of chondral lesions at the knee: A bovine cadaveric study

Abstract: Chondral lesions frequently occur in different topographic locations of the knee. This study evaluated the functional properties among the articulating surfaces of the tibiofemoral and patellofemoral joints, and whether neo-cartilage engineered using chondrocytes from different knee locations would reflect these differences. The biomechanical properties of bovine cartilage isolated from eight locations within the tibiofemoral (medial and lateral condyle, medial and lateral tibial plateau) and patellofemoral jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Non‐destructive optical parameter FLIm CH1 LT was significantly increased with +LOX treatment (g) and FLIm CH3 LT was significantly increased with +LOX and + LOX + LINK (h) over CTL. Red dashed lines represent native values (Paschos, Lim, Hu, & Athanasiou, ) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non‐destructive optical parameter FLIm CH1 LT was significantly increased with +LOX treatment (g) and FLIm CH3 LT was significantly increased with +LOX and + LOX + LINK (h) over CTL. Red dashed lines represent native values (Paschos, Lim, Hu, & Athanasiou, ) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
“…Neocartilage constructs with +LOX and +LINK treatments had tensile properties on par with those of native, juvenile femoral cartilage, and the compressive relaxation modulus reached 86% of native values (300 kPa compared with 350 kPa for the native tissue; Paschos et al, ). The lower proteoglycan content at 4 weeks in culture (~7% in neocartilage as compared with ~14% in native tissue; Paschos et al, ) may partially account for lower compressive stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Withstand in vivo forces during the joint movement operation (mechanical and structural stability of the biomaterial in the meniscus area needs to be able to withstand compressive and tensile forces (these forces have been aptly described in Paschos et al (2017) );…”
Section: Biomaterialsmentioning
confidence: 99%
“…Cartilage lesions are among the most often recognized pathologies in young adults undergoing arthroscopy. Approximately 60% of the patients treated arthroscopically for any reason had at least one chondral lesion at their knee[ 1 ]. Due to the relatively young age of these patients (mean age ranged from 37 to 43 years old) and because the majority of lesions has been graded as II or III, it was suggested that impending osteoarthritis would be inevitable without treatment in these patients[ 1 ].…”
Section: Introductionmentioning
confidence: 99%